Pentingnya Bimbingan Konseling Dalam Pemberdayaan Masyarakat Komunitas Lansia - Azalia, Banowati; Kinasih, Gracia Putri; Aulia, Gabriel; M, Muslikah; Mahfud, Ashari (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Guidance and counseling have an important role in community empowerment, especially the elderly community. This article aims to examine the urgency of guidance and counseling in improving the welfare of the elderly through a psychosocial approach and community empowerment. The scope of the study includes emotional, social, and mental aspects that affect the quality of life of the elderly. This article highlights how guidance and counseling can improve the quality of life of the elderly by providing psychological support, facilitating social interactions, and empowering them in various community activities. Through individual and group approaches, counseling can help the elderly find the meaning of life, increase self-confidence, and overcome stress due to age-related changes.